IMPACTS OF TEACHER ELECTRONIC FEEDBACK ON EFL STUDENTS' WRITING - Wiliyanti, Cici Riksa (2017)
The introduction of technologies into educational environments has made it possible for teachers and students to communicate their ideas, information, and feelings without any limit on time and space. It helps to enhance learning and to speed communication and it shifts handwritten feedback into electronic feedback, which covers a range of often dissimilar approaches to the teaching of writing. Thus, the emergence of electronic feedback seemed to be one promising solution to give teachers more space in providing feedback. This experimental study aimed at investigating the impact of three different types of teacher electronic feedback: teacher feedback through the comment function on the students' essay in the form of a word-processed text sent by email only, teacher feedback through the comment function on the students' essay in the form of a word-processed text sent by email followed by online discussion and no electronic feedback condition. This study also aims to discover the students' attitude toward the implementation of teacher electronic feedback. It involved three classes consisting of 90 second graders at one of senior high schools in Bandung. The data were gathered from pretest, posttest and interview. The obtained data were analyzed based on The ESL Composition Profile proposed by Jacob et al (1981). The statistical computation showed that the two types of teacher electronic feedback technique are both likely effective in improving students' writing quality. Furthermore, most students tended to respond positively toward the electronic feedback provided by their teacher as they considered it helpful to make them write better. In conclusion, teacher electronic feedback has been proven to be able to improve students' writing quality especially in the language use aspect. However, some issues reported which cover the practical problem in opening Edmodo platform and resulted students' lack of interest in joining the online discussion session. _ ; _ Pengenalan teknologi ke dalam lingkungan pendidikan telah memungkinkan guru dan siswa untuk mengkomunikasikan ide-ide, informasi, dan perasaan mereka tanpa batas ruang dan waktu.Hal ini membantu untuk meningkatkan pembelajaran dan untuk mempercepat komunikasi dan menggeser umpan balik dengan tulisan tangan menjadi umpan balik melalui elektronik, yang mencakup berbagai pendekatan pengajaran menulis. Dengan demikian, munculnya umpan balik elektronik tampaknya menjadi salah satu solusi yang menjanjikan untuk memberikan guru lebih banyak ruang dalam memberikan umpan balik. Penelitian eksperimental ini bertujuan untuk menyelidiki dampak dari tiga jenis umpan balik elektronik guru: tanggapan guru melalui fungsi komentar pada esai siswa dalam bentuk teks kata-diproses dan dikirim melalui email saja, umpan balik guru melalui fungsi komentar pada esai siswa dalam bentuk teks kata-diproses dan dikirim melalui email dan diikuti dengan diskusi online dan kondisi umpan balik tanpa bantuan elektronik. Penelitian ini juga bertujuan untuk mengetahui sikap siswa terhadap pelaksanaan umpan balik elektronik guru. Ini melibatkan tiga kelas yang terdiri dari 90 siswa kelas dua di salah satu SMA di Bandung. Data dikumpulkan dari pretest, posttest dan wawancara. Data yang diperoleh dianalisis berdasarkan The ESL Composition Profile yang diusulkan oleh Jacob et al (1981). Perhitungan statistik menunjukkan bahwa dua jenis teknik umpan balik guru elektronik efektif dalam meningkatkan kualitas menulis siswa. Selain itu, sebagian besar siswa cenderung merespon positif terhadap umpan balik elektronik yang disediakan oleh guru mereka karena mereka menganggap itu bermanfaat untuk membuat mereka menulis dengan lebih baik. Kesimpulannya, umpan balik elektronik guru telah terbukti dapat meningkatkan kualitas menulis siswa terutama dalam aspek language use. Namun, beberapa masalah dilaporkan meliputi masalah praktis dalam membuka platform Edmodo dan mengakibatk